2022
DOI: 10.21203/rs.3.rs-2179598/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparative study of machine translated subtitles based on the user-centered approach: a case study between Bilibili and YouTube

Abstract: Bilibili has become a famous video-sharing platform in China, attracting a growing number of visitors. Expect for the videos made by uploaders themselves, an increasing number of videos in different languages are uploaded. This year, the platform announced that automatic translation can be used for free to offer an alternative solution to the language barrier. Previous research has been done to test the impact machine-translated subtitles of TED (Technology, Entertainment, and Design) or MOOCs (Massive Open On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…through data analysis. It has been concluded that most people can understand the content through machine translation, and writing bilingual is more acceptable [7].…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…through data analysis. It has been concluded that most people can understand the content through machine translation, and writing bilingual is more acceptable [7].…”
Section: Related Researchmentioning
confidence: 99%
“…Bilibili, nicknamed B site, has become a major video-sharing website in China, which hosts videos on various themes, including movies, technology, science, and anime [7]. Bilibili allows users to participate and co-build the boards they are interested in.…”
Section: Business Differencesmentioning
confidence: 99%